2016
DOI: 10.1177/0192623316642527
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing “Adversity” of Pathology Findings in Nonclinical Toxicity Studies

Abstract: The identification of adverse health effects has a central role in the development and risk/safety assessment of chemical entities and pharmaceuticals. There is currently a need for better alignment regarding how nonclinical adversity is determined and characterized. The European Society of Toxicologic Pathology (ESTP) therefore coordinated a workshop to review available definitions of adversity, weigh determining and qualifying factors of adversity based on case examples, and recommend a practical approach to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
91
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(93 citation statements)
references
References 33 publications
1
91
1
Order By: Relevance
“…A more challenging question is whether non-a2u accumulations (e.g., hyaline droplets) in the tubular epithelium of female rats should be considered adverse. This latter scenario would be interpreted on a case-by-case basis integrating other renal effects, distribution and severity of accumulation, reversibility, and other knowledge about the compound being studied (Palazzi et al 2016).…”
Section: Alpha-2u Globulin Accumulationmentioning
confidence: 99%
“…A more challenging question is whether non-a2u accumulations (e.g., hyaline droplets) in the tubular epithelium of female rats should be considered adverse. This latter scenario would be interpreted on a case-by-case basis integrating other renal effects, distribution and severity of accumulation, reversibility, and other knowledge about the compound being studied (Palazzi et al 2016).…”
Section: Alpha-2u Globulin Accumulationmentioning
confidence: 99%
“…Several recent publications aimed to provide guidance in determining adversity in preclinical toxicology studies (ECETOC, 2002, Lewis et al ., 2002, Dorato and Engelhardt, 2005, Keller et al ., 2012, Kerlin et al ., 2016, Palazzi et al ., 2016). The readers are encouraged to refer to these publications for more in depth information on adversity in toxicology studies.…”
Section: Introductionmentioning
confidence: 99%
“…The readers are encouraged to refer to these publications for more in depth information on adversity in toxicology studies. Due to the increased interest in the topic of adverse versus adaptive responses in toxicology studies, several recent workshops, and symposia were organized by the American College of Toxicology (Cavagnaro and Beilke, 2014, Kiorpes and Pandiri, 2014), the Society of Toxicologic Pathology (Kerlin et al ., 2016), and the European Society of Toxicologic Pathology (Palazzi et al ., 2016). This continuing education course at the 2016 STP annual meeting in San Diego, CA, aims to provide a forum to disseminate information and to enable discussion within the STP membership.…”
Section: Introductionmentioning
confidence: 99%
“…These recommendations are based on general principles that are well considered and broadly applicable, but are largely focused on anatomic pathology and provide limited guidance for CP. In a recent complementary effort, the European Society of Toxicological Pathology (ESTP) coordinated an international workshop to further characterize the concept of adversity and to frame discussions specific to particular organs or types of lesions (Palazzi et al 2016). One workshop session of the ESTP working group concluded that CP changes should not be considered adverse in isolation without consideration for associated anatomic pathology findings and adverse in-life outcomes.…”
mentioning
confidence: 99%
“…One workshop session of the ESTP working group concluded that CP changes should not be considered adverse in isolation without consideration for associated anatomic pathology findings and adverse in-life outcomes. The current article applies the fundamental principles identified in Kerlin et al (2016) and Palazzi et al (2016) to the specific challenges of adversity determination in CP. Here, toxicologic clinical pathologists representing the Regulatory Affairs Committee (RAC) of the American Society of Veterinary Clinical Pathology (ASVCP) and the Clinical Pathology Interest Group (CPIG) of the STP delineate overarching principles and unique considerations for assessing adversity in CP data interpretation.…”
mentioning
confidence: 99%